Genetic diversity of Echinococcus multilocularis and Echinococcus granulosus sensu lato in Kyrgyzstan: The A2 haplotype of E. multilocularis is the predominant variant infecting humans - Alvarez Rojas, Cristian A. (PLoS Negl Trop Dis, 2020)
Alveolar and cystic echinococcosis (AE, CE) caused by E. multilocularis and E. granulosus s.l., respectively, are considered emerging zoonotic diseases in Kyrgyzstan with some of the world highest regional incidences. Little is known regarding the molecular variability of both species in Kyrgyzstan. In this study we provide molecular data from a total of 72 parasite isolates derived from humans (52 AE and 20 CE patients) and 43 samples from dogs (23 infected with E. multilocularis and 20 with E. granulosus s.l.).Genetic variability in E. multilocularis was studied using the concatenated complete sequences of the cob, nad2 and cox1 mitochondrial genes adding a total of 3,558bp per isolate. The cob/nad2/cox1 A2 haplotype was identified in 63.4% of the human and in 65.2% of the dog samples. This haplotype was originally described in samples from Kazakhstan and St. Lawrence Island (Alaska, USA). We also describe here 16 non-previously defined variants of E. multilocularis (called A11-A26). All haplotypes cluster together within the Asian group in the haplotype network. Based on Fst values, low level of genetic differentiation was found between the populations of E. multilocularis isolated from different regions within the country. However, high degree of differentiation was found when all the concatenated sequences from Kyrgyzstan are considered as a single population and compared with the population of the parasite from the neighbouring country China. In the case of E. granulosus s.l. the analysis was based in 1,609bp of the cox1 gene. One isolate from a dog was identified as E. equinus, while all the other sequences were identified belonging to E. granulosus s.s. In total, 24 cox1 haplotypes of E. granulosus s.s. were identified including the already described variants: Eg01 (in 6 samples), Eg33 (in 4 samples), EgCl04 (in 2 samples), Eg03 (in 1 sample) and Eg32 (in 1 sample). From the twenty-five other isolates of E. granulosus s.s. a total of 19 non-previously described cox1 haplotypes were identified and named as EgKyr1 to EgKyr19. The most common haplotype infecting human is the EgKyr1 which was found in 5 isolates.The cob/nad2/cox1 A2 haplotype of E. multilocularis is responsible for the majority of human infections in Kyrgyzstan and is also found in the majority of dogs included in this study. Further similar studies in different parts of Asia could elucidate if it is also the most common variant infecting humans in other countries. It remains unknown if this particular haplotype presents differences in virulence which could have contributed to the emergency of alveolar echinococcosis in Kyrgyzstan. In the case of E. granulosus s.s. it seems that there is no dominant haplotype infecting humans in Kyrgzstan. Further characterization of biological or antigenic features of dominant mitochondrial haplotypes could help to elucidate if they present differences which could be relevant in the diagnostic, pathogenicity or in the host/parasite interaction when infecting humans.